2011
DOI: 10.1002/ajmg.c.30288
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of cobalamin absorption and metabolism

Abstract: Derivatives of cobalamin (vitamin B(12)) are required for activity of two enzymes in humans. Adenosylcobalamin is required for activity of mitochondrial methylmalonylCoA mutase and methylcobalamin is required for activity of cytoplasmic methionine synthase. Deficiency in cobalamin, or inability to absorb cobalamin normally, can result in accumulation of methylmalonic acid and homocysteine in blood and urine. Methylmalonic acidemia can result in metabolic acidosis which in severe cases may be fatal. Hyperhomocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(79 citation statements)
references
References 104 publications
2
73
1
Order By: Relevance
“…Neutropenia had been noted in both dogs and, mild macrocytosis in the absence of anemia was detected in 1 dog at some point. These are typical findings described in children with congenital cobalamin deficiency 2, 14. Neutropenia was also reported in the only previously published case of a cobalamin‐deficient Beagle 4.…”
Section: Discussionsupporting
confidence: 74%
“…Neutropenia had been noted in both dogs and, mild macrocytosis in the absence of anemia was detected in 1 dog at some point. These are typical findings described in children with congenital cobalamin deficiency 2, 14. Neutropenia was also reported in the only previously published case of a cobalamin‐deficient Beagle 4.…”
Section: Discussionsupporting
confidence: 74%
“…To date, mutations in genes for 10 cellular complementation groups based on patient-derived fibroblasts have been identified, thereby providing insight into the intracellular trafficking and biochemistry of B 12 (Watkins and Rosenblatt, 2011, 2016). A recent GWAS studies for low circulating B 12 levels in human have revealed its association with 11 loci (Grarup et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The advances in biology have led to the identification of pathways, proteins and genes involved (119). The structural and functional characterization of proteins involved and the metabolic consequences of gene defects have provided a better understanding of clinical disorders of Cbl metabolism (120) to implement strategies to manage these disorders.…”
Section: Introductionmentioning
confidence: 99%